Pelatihan Menumbuhkan Jiwa Kewirausahaan Pada Pelajar SMPN 8 Kecamatan Pelalawan - Assyifa, Zubaidah; Winario, Mohd (EL-EMIR INSTITUTE, 2025)
Fostering an entrepreneurial spirit from an early age is essential in shaping a generation that is independent, creative, and innovative. Junior high school students, particularly those at SMPN 8 Pelalawan District, require entrepreneurial training to help them recognize their potential and identify business opportunities in their surroundings. This study aims to determine the effectiveness of training in cultivating an entrepreneurial spirit among students. The method used is a participatory approach involving training sessions, discussions, simple business practices, and evaluations. The results show an increase in students’ interest and understanding of entrepreneurship concepts, as evidenced by the emergence of creative business ideas and entrepreneurial enthusiasm among most participants. The training also demonstrated that hands-on practical approaches are more effective than lecture-based sessions alone. The study recommends that schools continuously provide entrepreneurship training and incorporate it into extracurricular activities to support students' character development and independence